Risk of metabolic syndrome in the first degree relatives of women with polycystic ovarian syndrome - M., Yashwant A.; Kokiwar, Prashant R.; Taiseen, Gazala (International Journal Of Community Medicine And Public Health, 2017)
Background: Poly cystic ovarian syndrome (PCOS) is a common disorder, affecting approximately 4 – 8% of women in the reproductive age group. First degree relatives (FDRs) of women with PCOS are at high risk developing endocrine and metabolic co-morbidities of PCOS such as obesity, insulin resistance (IR), and impaired insulin sensitivity, hyperlipidemia and metabolic syndrome (MBS). Present study was conducted with the objectives to evaluate the risk of metabolic syndrome in FDRs of women with PCOS and to compare the risk of metabolic syndrome in FDRs of women with PCOS with age, sex and relation matched FDRs of women with no PCOS. To give suitable recommendations based on the findings of the study. Methods:Hospital based cross sectional analytical study was carried out. 50 FDRs of women with PCOS were compared against same number of age, sex and relation matched FDRs of women with no PCOS. Results: The prevalence of MBS was significantly higher i.e. 34% among FDRsPCOS compared to FDRsControls (8%) (p < 0.05). The FDRsPCOS were 5.92 times more at risk of MBS than FDRsControls (p < 0.05). Relation wise it was found that the fatherPCOS and motherPCOS were 1.5 times at risk, brotherPCOS were 14.26 and sisterPCOS were 12.43 times at risk of MBS than their counterparts. Conclusions:Thus it is concluded that the FDRsPCOS are at high risk of MBS than FDRsControls.